Sex Disparities in Effects of Cystic Fibrosis-Related Diabetes on Clinical Outcomes: A Matched Study - Robert J Miller; Hugh D Tildesley; Pearce G Wilcox; Hongbin Zhang; Stuart H Kreisman (Canadian Respiratory Journal)
BACKGROUND: Cystic fibrosis-related diabetes (CFRD) is an increasingly prevalent comorbidity factor for patients with cystic fibrosis (CF). CFRD has been associated with an accelerated decline in clinical parameters and an increased mortality rate.